New insights on clinical perspectives of FLASH radiotherapy: from low- to very high electron energy - Ursino, Stefano; Gadducci, Giovanni; Giannini, Noemi; Gonnelli, Alessandra; Fuentes, Taiushia; Di Martino, Fabio; Paiar, Fabiola (Frontiers in Oncology, 2023)
Radiotherapy (RT) is performed in approximately 75% of cancer patients and its efficacy is often hampered by the low tolerance of the surrounding normal tissues. Recent advancements have demonstrated the potential to widen the therapeutic window through the use of "very short" radiation treatment delivery (from a conventional dose rate between 0.5-2Gy/min to more than 40Gy/s) causing a significant increase of normal tissue tolerance without varying the tumor effect. This phenomenon is called “FLASH Effect (FE)” and has been discovered by using electrons. Despite several physical, dosimetric and radiobiological aspects need to be still clarified, current preclinical “in vivo” studies reported a significant protective effect of FLASH RT on neurocognitive function, skin toxicity, lung fibrosis and bowel injury. Therefore, the current radiobiological premises lay the foundation for groundbreaking potentialities in clinical translation that could be addressed to an initial application of Low Energy Electron FLASH (LEE) for the treatment of superficial tumors to a subsequent Very High Energy Electron FLASH (VHEE) for the treatment of deep tumors. Herein, we report a clinical investigational scenario that, if supported by the forthcoming preclinical studies, could be drawn in a near future.